Ratio Decidendi Judge's Decision In Deciding The Crime Of Persecution - Sintia Husain (Universitas Negeri Gorontalo, 2020)
This study aims to find out the ratio of judge's decision in deciding the crime of child abuse based on verdict number 17 / Pid.Sus-Anak / 2019 / PN. Gto. The method used in this study is normative legal research. The approach used is to use the legal approach or statute approach (statute approach) and use the case approach. The results showed that the ratio decidendi the judge's ruling in deciding the crime of persecution based on the verdict number 17 / Pid.Sus-Anak / 2019 / PN. Gto. It is appropriate because this is considering the age of the defendant who is under 18 (eighteen) years old. In Article 1 number 1 of Law No. 35 of 2014 concerning Amendments to Law No. 23 of 2002 on Child Protection it is stated that a child is someone who is not yet 18 (eighteen) years old, including children who are still in the womb. In other words, the accused is still classified as a child according to the criminal law and is considered still unable to account for the actions committed. Therefore, there needs to be a change in the Child Protection Act related to children as